On the development trends of the German language in the classroom (Philology, 2024)
It is well known that the change of the language topic and its development in foreign language lessons are of great importance. The material and competence dimension at school levels is becoming increasingly large-scale thematically and makes a clear emphasis both quantitatively and qualitatively at the upper levels of the gymnasium. And if we consider what changes have taken place at the state level in Germany, then we have the German language after 1945 and the German language after reunification, when linguistic changes are simply inevitable here.What are the developmental trends, and which of them are decisive for modern language? Does language change as a whole, or do only certain areas change? How are linguistic norms or patterns established? Answers to these and other questions require an understanding of the “linguistics of language change,” which is an extremely complex and richly literary area of linguistics.In this context, in order to correctly develop students’ knowledge of a foreign language, teachers need the following subcompetencies: 1) a special ability to observe and perceive language in a transitional period; 2) linguistic analysis and the ability to explain identified “deviations” and “cases of doubt”; 3) the ability to evaluate linguistic doubts or trends in language development.For this purpose, it is recommended to use more open, collaborative forms of teaching and learning that promote discovery-based learning and scientific-propaedeutic work.To sum up, we note that two important criteria are necessary when teaching a foreign language. These are: confident handling of linguistic foreignness and competence.
Keywords: lexis; German language; language changes; trends